2005
DOI: 10.1007/bf03404022
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions About Hearing Protection and Noise-induced Hearing Loss of Attendees of Rock Concerts

Abstract: Background: This study examines perceptions of rock concert attendees about risk of noise-induced hearing loss (NIHL) and use of hearing protection at a busy Toronto rock concert venue. Methods: Two hundred and four questionnaires were completed and returned (75% response rate) by attendees at four rock concerts. Results:The respondents had an average age of 20.6 years and 55.4% were male. Thirtyfour point three percent (34.3%) thought that it was somewhat likely and 39.8% thought it was very likely that noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
57
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 14 publications
7
57
1
5
Order By: Relevance
“…[1] One possible explanation may be that the individual attitude toward noise is affected by one's own experiences, which may influence how an individual chooses to act in a noisy situation. [2] The prevalence of tinnitus varies between different studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] One possible explanation may be that the individual attitude toward noise is affected by one's own experiences, which may influence how an individual chooses to act in a noisy situation. [2] The prevalence of tinnitus varies between different studies.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be explained by factors like the context, how the question regarding tinnitus is formulated and the definition of temporary and permanent tinnitus. [3] Bogoch et al, [1] conducted a study in which they asked people in line to a rock concert if they had experienced tinnitus, at any time and 84.7% answered yes. Davis [4] also made a study on the prevalence of tinnitus and found that 45% had at least on one occasion experienced tinnitus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6,7,8] In fact, college students are exposed regularly to noisy situations that exceed NIOSH recommended sound intensity limits. [9] For example: Music concerts, 92-110 dB(A); [10] nightclubs, 96-110 dB(A); [11] sporting events, 100-140 dB(A); [12,13] and use of portable listening devices, 90 -120 dB(A). [14,15] In addition, various studies have shown that young adult survey respondents (age 19-27 years) report frequent symptoms of NIHL including temporary hearing threshold shift (61%), tinnitus (43%), and/or ear pain (28%) after participating in leisure activities associated with hazardous noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…[3,18] Some possible reasons for this include discomfort, design, lack of knowledge about NIHL, and peer pressure. [10,18] It has been proposed, however, that young adults would be more likely to take precautions if they understood that they were personally vulnerable to permanent NIHL. [9] It is imperative, therefore, to determine if prevention programs targeting young people can effectively convey the risk of NIHL and change their behavior to help reduce risk of NIHL.…”
Section: Introductionmentioning
confidence: 99%